2023
DOI: 10.3390/scipharm91030040
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Activity, In Silico Analysis, and Molecular Docking Study of Verbascoside from Leucophyllum frutescens in Rats with Post-Necrotic Liver Damage

Osmar Antonio Jaramillo-Morales,
Erik Díaz-Cervantes,
Lisa Dalla Via
et al.

Abstract: There is an urgent need for scientists to verify the pharmacological properties of medicinal plants. Leucophyllum frutescens (Lf) belongs to the family Scrophulariaceae, and it is used in the treatment of airway diseases such as cough, tuberculosis, and asthma. The methanolic extract of the aerial parts of Lf allows for the isolation and identification of verbascoside (Vb). This study aimed to evaluate the hepatoprotective effect of Vb, a caffeoyl phenylethanoid glycoside (CPG), on post-necrotic liver damage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Recently, it was observed that intragastrical VB (20 mg/kg of body weight) from Leucophyllum frutescens extract, administered for 4 days, can preserve the integrity of liver cell membranes and lower blood concentration of aspartate aminotransferase and alanine aminotransferase in rats with induced necrotic damage. However, the mechanism of action of VB on liver protection is still not completely understood [52].…”
Section: Other Biological Activitiesmentioning
confidence: 99%
“…Recently, it was observed that intragastrical VB (20 mg/kg of body weight) from Leucophyllum frutescens extract, administered for 4 days, can preserve the integrity of liver cell membranes and lower blood concentration of aspartate aminotransferase and alanine aminotransferase in rats with induced necrotic damage. However, the mechanism of action of VB on liver protection is still not completely understood [52].…”
Section: Other Biological Activitiesmentioning
confidence: 99%